First-line ICIs in renal cell carcinoma - Vincenzo Fiorentino; Pietro Tralongo; Luigi Maria Larocca; Cristina Pizzimenti; Maurizio Martini; Francesco Pierconti (Taylor & Francis Group, 2023)
Treatment of metastatic renal cell carcinoma (mRCC) has radically changed, switching from interferon alfa (IFN-α) and high-dose interleukin−2 (HD IL−2) to new targeted therapies directed against tumoral neoangiogenesis, the mammalian target of the rapamycin (mTOR) pathway and immune checkpoints. Of note, the inhibition of immune checkpoints restores antitumor immune response, therefore promoting immune-mediated elimination of neoplastic cells. The best example of this targeted treatment is represented by PD-1/PD-L1 inhibition that has become the standard of care in mRCC treatment and has improved mRCC patients' prognoses after failure of other targeted therapies. In this manuscript, we review the main therapeutic protocols adopted for mRCC, based on the use of immune checkpoint inhibitors (ICIs) alone or combined with other drugs.